Environmental design and thermal comfort in urban courtyards within different urban design patterns in Saudi Arabia - Alosimi, Turki (2025)
Urban open space design and patterns play a vital role in shaping the microclimate of outdoor environments, significantly influencing user comfort and activities. In a harsh arid environment like that of Saudi Arabia, creating high-quality, thermally comfortable outdoor urban spaces is critical. However, studies have highlighted the lack of detailed policies for the environmental planning and design of outdoor urban spaces in Saudi cities, particularly in Makkah, contributing to increased thermal discomfort.